Graphitic carbon nitride with S and O codoping for enhanced visible light photocatalytic performance. Issue 26 (10th March 2017) - You, Ran; Dou, Hailong; Chen, Lu; Zheng, Shaohui; Zhang, Yongping
Abstract : Facile synthesis of the S, O codoped g-C3 N4 photocatalysts. Abstract : Graphitic carbon nitride (g-C3 N4 ) shows great possibility to enhance its visible light photocatalytic performance by tuning its electronic structure and band gap via nonmetal element doping. S and O codoped g-C3 N4 is synthesized by the polymerization of melamine and H2 O2 bonded trithiocyanuric acid (TCA) at an elevated temperature and characterized as crimped nanosheets with mesoporous structures. The photocatalytic performance of S–O codoped g-C3 N4 for RhB degradation increases 6 fold by enhancing visible light adsorption and decreasing its band gap compared to pristine g-C3 N4 nanosheets. The substitution of the edge N with S and O dopant causes much more strongly delocalized HOMO and LUMO and increases the number of reactive sites, facilitating the migration of photogenerated electron/hole pairs.